"Read it to me" Una estrategia didáctica para el fortalecimiento de la competencia comunicativa en inglés "Read it to me" A didactic strategy to strengthen the communicative competence in English - González Valencia, Heriberto (Universidad Santiago de Cali, 2020)
This article refers to the importance to reading process as a didactic sequence to improve the communicative competence in EFL using children literature and integrating ITC tools to support a private school in Cali-Colombia. This research followed an action research design applied during a period of ten weeks and formulated by Kemmis y MC Taggart (1988). The information was gathered through interviews, surveys, participant observation and a field journal. This data was analyzed by a process of categorization, statistical analysis and a theoretical contrast between the results and previous studies about language learning. The findings suggested that this didactic sequence was beneficial in terms of its pedagogical impact, its use of children literature integrating ICT technologies for the homeroom teacher and her students.